USE OF VERMAL FOR HANHULETERAKOZ OF DUCKS AND ITS INFLUENCE ON BIOCHEMICAL INDICES OF WHEY OF BLOOD - Богач, М. В.; Шайдюк, І. В. (Scientific Progress & Innovations, 2014)
The article of experimental ganguleterakos invasion of ducks is determined the efficacy of anti-parasitic drugs "Vermal" (NSC "IECVM"), which accounted 90,9% and 95,6 % - IE. Applied "Vermal" led immunosuppressive effect about 3-10 days after use, and since 10 days the preparation normalized the content of total protein and globulin fractions resulted in a decrease in CIC of 0,21±0,02 mg/ml to 0,11±0,02 mg/ml and seromucoid of 0,18±0,02 mg/ml to 0,12±0,01 mg/ml in the blood of ducks.